Molecular pathology of chromophobe renal cell carcinoma: a review - Yusenko, Maria (International journal of urology, 2010)
The recognition of chromophobe renal cell carcinoma (RCC) among other distinct types of renal cell tumors (RCT) based on light-microscopic features, such as cytoplasmic and nuclear characteristics, might pose a dilemma in some cases because of morphological pattern overlapping with renal oncocytoma or conventional RCC. The present article reviews chromophobe RCC with focus on aspects of its molecular pathology, which was shown using ancillary modern microarray-based technology that can distinguish it from its mimics and therefore be helpful for its correct diagnosis. Although the high resolution DNA-microarray analyses excluded with all certainty the occurrence of small specific alterations, the loss of entire chromosomes 2, 10, 13, 17 and 21 occurs exclusively in chromophobe RCC and therefore probes localized at these chromosomes might be used to establish the diagnosis of chromophobe RCC in cases with uncertain histology. The usefulness of proposed candidate genes selected by the global gene expression analyses in the diagnostic pathology is far below expectations. The conflicting staining patterns, together with the poor specificity of used antibodies, leads us to believe that these candidate immunomarkers might not help in the separation of chromophobe RCC, with the exception of CD82, which has recently been suggested to be used for routine histological diagnosis.